Integrating Physiotherapy into Primary Health Care in Nigeria: Perceptions of Primary Health Care Practitioners (2022)
The perception of Primary Health Care (PHC) practitioners about integrating physiotherapy into PHC in Nigeria is still unknown. The aim of this study was to examine the knowledge and attitude of PHC practitioners in Nigeria regarding the integration of physiotherapy into PHC. The participants in this cross- sectional study were 183 PHC practitioners (physicians, nurses, and community health workers). A content-validated, semi-structured questionnaire was used to obtain information about history of exposure to physiotherapy, knowledge, and attitudes toward integrating physiotherapy into PHC. Data was analyzed using Pearson's product moment correlation and Analysis of Variance at a = 0.05. Participants were mostly females (n = 154; 84.2%) and aged 39.97 ± 9.38 years. The mean years of work experience was 14.41 ± 8.68 years. Participants had limited knowledge about the role and scope of physiotherapy but were willing to learn more about physiotherapy. Less than half of the participants however, had favorable attitude toward integrating physiotherapy into PHC. Knowledge differed significantly across healthcare professions (p < .05) and was significantly correlated with attitude (p < .01). Our findings underscore the importance of interprofessional education and teamwork among healthcare providers. This might enhance understanding, modify attitudes and facilitate the inclusion of physiotherapy into PHC in Nigeria. Additionally, this could improve access to physiotherapy services for Nigerians.